Naming disorder in Alzheimer’s disease patients - Οκαλίδου Αρετή; Τσολάκη Μάγδα; Σαραφίδου Γιασεμί; Καζής Αριστείδης (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF